Pengaruh Iklan, Citra Merek Dan Harga Terhadap Minat Beli Produk Le Minerale - Ismi Munfarida; Nurullia Rizkyani; Rayhan Gunaningrat (STIKes Ibnu Sina Ajibarang, 2024)
This research was conducted to determine and explain the influence of advertising, brand image and price on interest in purchasing Le Minerale products. The research was carried out by distributing questionnaires online using Google Form. This research uses quantitative methods, the population in this research is consumers who use Le Minerale products in the Greater Solo area with a sample size of 105 respondents. The research was carried out with the help of the SPSS 27.0 application as a tool for calculating data obtained using 4 variables, the independent variable is advertising, brand image and price, while the dependent variable is purchase interest. The analysis used in this research is the classical assumption test, multiple linear regression and hypothesis testing. The results of the F Test research obtained a calculated F value of 13.139 > 2.460 with a significance value of 0.000 < 0.05 so it can be concluded that advertising, brand image and price simultaneously influence purchasing interest.